On the Exact Series Solution for Nonhomogeneous Strongly Coupled Mixed Parabolic Boundary Value Problems - Vicente Soler (Abstract and Applied Analysis, 2014)
An exact series solution for nonhomogeneous parabolic coupled systems of the type ut-Auxx=Gx, t, A1u0, t+B1ux0, t=0, A2ul, t+B2uxl, t=0, 0<x<1, t>0, ux, 0=fx, where A1, A2, B1, and B2 are arbitrary matrices for which the block matrix is nonsingular, and A is a positive stable matrix, is constructed.